Respiratory Physiotherapy and Mother/Child Hospitalization - Evelyn Hilda Diaz Altamirano; Luciana Jereissati (Psicologia, 2002)
The way of approaching a child during the health-illness process has changed a lot, as a result of researches in medical, human and social areas. The hospitalization process in pediatric ward units doesn’t only involve the child, but also the mother who escorts the child, staying in hospital herself next to her child, causing a disruption in familiar life as the mother regards her other children and husband to second place. For the physiotherapy treatment to be successful and to minimize the situations of relapse in the internment of these children the mother-son relationship needs to be established and strengthened helping the mother to develop responsibilities to proceed with her child´s treatment in each situation possible (home based and/or ambulatory treatment), helping to build a more hopeful future and, above all, improving her child’s quality of life.